THE FABRICATION OF QUANTUM-WIRE STRUCTURES THROUGH APPLICATION OF CCL4 TOWARDS LATERAL GROWTH-RATE CONTROL OF GAAS ON PATTERNED GAAS SUBSTRATES - KIM, Y; PARK, YK; KIM, MS; KANG, JM; KIM, SI; HWANG, SM; MIN, SK (AMER INST PHYSICS, 1995)
We have observed the remarkable increase of GaAs lateral growth rate in the presence of CCl4 during metalorganic chemical vapor deposition (MOCVD) on patterned CaAs substrates. The lateral growth rate shows a linear dependence on CCl4 flow rate. On the other hand, the GaAs vertical growth rate is relatively insensitive to the CCl4 flow rate. The maximum ratio of lateral to vertical growth rate is about 14. Using these characteristics, we have fabricated CCl4-doped quantum wires (QWRs) on V-groove structures. The QWR structures show thickness enhancement factors, defined as the ratio of QWR thickness in the center region to the quantum well thickness in the nonpatterned region, as high as 5.6. (C) 1995 American Institute of Physics.
Keywords: VAPOR-PHASE EPITAXY; LAYERS